Investigations of Innovative Biomass Materials for Low Carbon Buildings - Wang, Yixin (2023)
The energy shortage, excessive consumption of oil resources and environmental pollution are the major problems worldwide, and there is an urgent need to improve and solve these problems. This thesis aims to develop novel, environmentally friendly biomass aerogels as thermal insulating, sound absorbing and filtering materials for low-carbon buildings. The biomass aerogels are made of natural materials and prepared through sol-gel, ageing and freeze drying methods to have advantageous properties of low density, high specific surface area and high porosity. The work will be divided into seven sections as follows: 1) Overview of the current status of biomass aerogels; 2) Selection of the starting materials and evaluate the characteristics of composite biomass mixtures/gels; 3) Preparation of sound absorbing biomass aerogels and the performance testing; 4) Preparation of thermal insulating biomass aerogels and properties measurement; 5) Production of biomass aerogels with promising filtration performance; 6) Simulation and evaluation of the energy saving of a retrofitted house with biomass aerogel as the insulator; 7) Economic and environmental assessment of biomass aerogels. This research selected Konjac glucomannan, starch, gelatin and wheat straw as the starting materials. The biomass mixtures/gels were prepared through sol-gel and ageing processes. Meanwhile, the biomass aerogels were produced by the freeze drying method. In these initial experiments, systems' pasting properties, rheological properties and microstructure were tested and observed to explore the influence of process parameters and different addition ranges of raw materials on the biomass mixtures/gels. Based on the results, raw materials dissolution temperature was chosen as 95°C, the recommended amount of KGM is about 1% (w/v), and the ageing process must be carried out under 37°C. The characteristic experiments were conducted on three types of biomass aerogels with different compositions for three applications: sound absorption, thermal insulation and filtration. KGM, gelatin and wheat straw were selected to produce sound absorbing biomass aerogels. Results show that gelatin addition can significantly improve sound absorption performance at medium/high frequencies and mechanical strength. The small amount of wheat straw addition improves sound absorption property, but it is reduced with more content added. Better sound absorption performance is achieved than sound absorption cotton, while the best result is obtained with an average noise reduction coefficient of 0.38, and the coefficient reaches 0.88 at 4500 Hz. Wheat straw addition also leads to strength reduction but enhancement when the addition is more than 1%, where fine wheat straw bars form nest structures for strengthening. For thermal insulation, test results show that the appropriate wheat straw length and pre-freeze temperature greatly influence thermal insulation properties of biomass aerogels. With wheat straw sieved through 120 mesh, K1G0.5S2WS1.5 aerogel had a thermal conductivity of 0.0420 Wm-1K-1. When the pre-freeze temperature further decreased to -30°C and -40°C, the thermal conductivities of K1G0.5S2WS1.5 aerogels were reduced to 0.0375 and 0.0327 Wm-1K-1, respectively. For filtration properties, the biomass aerogel K0.9G1.8S3.6WS1.8 shows excellent performance in removing particulate matter 2.5 (PM 2.5) (99.50%) and PM 10 (99.40%) from the environment in an actual room with small thickness. Numerical modelling was conducted to investigate the energy saving of a retrofitted E.ON house with biomass aerogel as insulation layers. Meanwhile, the economic and environmental analysis results show that applying these novel biomass aerogels in low carbon buildings is valuable.